Kepastian Hukum Penguasaan Tanah oleh Pemerintah Daerah yang Berasal dari Peminjaman dalam Sengketa dengan Ahli Waris (Studi Putusan Mahkamah Agung Nomor 3580 K/Pdt/2023) - Marihot Doni Putra Sitanggang; Muhammad Yamin Lubis; Rosnidar Sembiring (CV Rewang Rencang, 2025)
Land ownership disputes between local governments and heirs become increasingly complex when involving land that originally came from a loan arrangement. The case of Lapangan Akso Dano in Supreme Court Decision No. 3580 K/Pdt/2023. The research problems include: first, the legal certainty of land possession status by the local government; second, the legal Construction for protecting regional assets originating from loaned land that has been physically possessed for an extended period; and third, the legal analysis of the judges’ considerations in Supreme Court Decision No. 3580 K/Pdt/2023 regarding land ownership disputes involving loaned land to the local government. This research employs a normative juridical method. The study reveals that legal certainty over land possession by local government is comprehensively regulated through a legal hierarchy from the 1945 Constitution to Government Regulation No. 24/1997, reinforced by customary law recognition of long-term physical possession.